Carbon sequestration in graphene oxide modified cementitious system. (15th December 2022) - Mishra, Geetika; Warda, Ashraf; Shah, Surendra P.
Abstract: Graphene oxide is emerging as a promising nanomaterial owing to its unique property of being a strong and flexible material. This work examines the potential use of graphene oxide (GO) for CO2 sequestration in cementitious-based materials in addition to mechanical properties. The effect of oxidized graphene surface on the hydration mechanism of cement paste and carbonate mineralization was investigated. Experimental results show that the application of GO at optimum amount offers 40% improvement in compressive strength at an early age. Accelerated carbon curing of GO-cement matrix was performed to evaluate CO2 sequestration through thermogravimetric analysis and results revealed that adding a low concentration of GO (i.e. 0.05%) improved CO2 uptake by 30% in the cementitious system. Further, physical adsorption of CO2 molecules and alteration in C–S–H was confirmed by the FTIR study. This finding suggests that the application of GO, not only improved the mechanical properties but it significantly enhanced the CO2 sequestration in cementitious systems. Highlights: Graphene oxide (GO) has the potential to be used for CO2 sequestration in cement. Addition of graphene oxide improved the hydration kinetics of cement. Early-age compressive strength improved by 40% in GO blended cement. 30% higher CO2 can be absorbed and stored in GO-blended composites.